Web-based planner system: a user centric evaluation for university community / Nor Arzami Othman ... [et al.] - Othman, Nor Arzami; Osman, Mohd Nizam; Sedek, Khairul Anwar; Shamsuhaidi, Nurhasnisha (UiTM Cawangan Perlis, 2024)
This study introduces a web-based planner system developed to enhance the planning and scheduling processes within the academic environment. It is due to universities grapple with manual and fragmented planning processes, leading to inefficiencies, miscommunication, and a lack of real-time updates. The Agile methodology was employed to foster adaptability and responsiveness to changing requirements throughout the development lifecycle. The research focuses on the User Acceptance Test (UAT) phase, a crucial element in ensuring the system's functionality aligns with end-user expectations. A total of 36 respondents, comprising academic staff, students, and administrative personnel from UiTM Perlis, participated in the UAT process. The study investigates user satisfaction, system usability, and overall acceptance of the web-based planner system through a series of targeted assessments and surveys. Results indicate a positive reception among users, highlighting the system's effectiveness in streamlining planning processes and improving overall user experience. The Agile methodology's iterative nature facilitated realtime adjustments based on user feedback, ensuring that the final product meets the dynamic needs of the academic community. The findings contribute valuable insights into the successful integration of Agile methodologies in web-based system development and underscore the importance of user involvement in shaping functional and user-friendly solutions. This research not only showcases the benefits of web-based but also emphasizes the significance of user acceptance testing as a critical step in delivering solutions that truly resonate with end-users.